Online society in China : creating, celebrating, and instrumentalising the online carnival - Herold, David Kurt; Marolt, Peter (Media, culture, and social change in Asia series., 2011)
This book discusses the rich and varied culture of China's online society, and its impact on offline China.¨It argues that the Internet in China is a separate 'space', and is more than merely a technological or media extension of offline Chinese society.